Medical aspects of competitive diving - A popular summary of a private literature collection - Zimmermann, W. (Eigenverlag, 2007)
the author has, since 1985, compiled a bibliography on competitive diving with 3300 references to books and articles. The complete list of titles is directly accessible through www.springschool.nl. Press "diving literature" on the home page. The bibliography is presented as a pdf-file, which gives the reader the option to search for words in the document, e.g. the name of an author or a word in a title. After visiting this website you will never think again that there is not enough written material on the art of competitive diving. You just have to know where to look!